PEMANFAATAN PELAYANAN KESEHATAN DAN KELUARGA BERENCANA DI DAERAH TRANSMIGRASI DI SULAWESI TENGGARA - Tukiran Tukiran; Pande Made Kutanegara (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1996)
The improvement of health facilities has been a major priority of the government policy. It is related to the effort of controlling population growth by reducing fertility and mortality rate. In line with this, one issue is worthwhile to question: whether or not those facilities productively utilized by the local people. This research was conducted in Lambuya subdistrict, Kendari, Southeast Sulawesi, the area which is considered to be successful in the implementation of the family planning program. The utilization of health and family planning services, from the aspect of age, education, and resident of clients is quite satisfactory. Based on these three aspects, it is not surprising if they can rely on health andfamily planningproviders. Besides the health workers at the primary health care, there are 91 traditional healers who take over health problems. The awareness of the local people to revisit the primary health care after an initial treatment is more of a causative effect of the initiative of health providers, than the desire of the clients themselves. Effort on enlightenment by improving quality of information to the people is influential in making people utilized the services available at the primary health care.